2014
DOI: 10.1186/1865-1380-7-s1-o5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of medical students on brain death and organ donation

Abstract: To assess the knowledge, attitudes of medical students regarding brain death and organ donation from brain dead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, inadequate knowledge of the concept of "brain-death" may lead to inability to identify the patient as a possible donor. Bapat et al and Palanivelu et al also reported a lack of adequate knowledge regarding "deceased organ donors" amongst medical students [1,14]. 3.3% to 7% of the respondents did not know anything about the different categories of possible organ donors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inadequate knowledge of the concept of "brain-death" may lead to inability to identify the patient as a possible donor. Bapat et al and Palanivelu et al also reported a lack of adequate knowledge regarding "deceased organ donors" amongst medical students [1,14]. 3.3% to 7% of the respondents did not know anything about the different categories of possible organ donors.…”
Section: Discussionmentioning
confidence: 99%
“…Bapat U et al, and Palanivelu ET et al, also reported a lack of adequate knowledge regarding 'deceased organ donors' among medical students. 2,19 The results on attitude towards organ donation were found to be better among the male students as 80.47% of them considered themselves to be a future organ donor. However, both the male as well as female respondents felt the need for more information and knowledge regarding organ donation.…”
Section: Discussionmentioning
confidence: 98%